Financial Wellbeing of Non Profit Organisations in the Western Cape - Kreusch, Ashleigh (Department of Social Development, 2016)
It is not unknown that NonProfit Organisations (NPOs) across South Africa are failing in their objective to provide adequate service delivery. The current poor wellbeing of NPOs is largely attributed to a lack of funding. Poor funding refers to challenges regarding internal fundraising efforts, government grants as well as international donations. The struggle to raise adequate funds has not only negatively impacted the scope of service delivery, but has also contributed to the closure of NPOs throughout the country. NPO's financial struggles are compounded by their inadequate financial reporting and management. The poor and inconsistent financial reporting and management does not encourage funders to part with their money. The unfortunate ripple effect of the poor financial reporting and management is a downscaling in service provision or, in more severe circumstances, closure. This dissertation sets out to analyse the financial wellbeing of NPOs within the Western Cape. In doing so, it set out to: To discover and describe the current condition of financial reporting; To analyse the NPO's financial sustainability and lastly; and To explore the sources of funding of NPOs. The three aims were achieved through the use of a financial trend analysis and financial ratios.